Graphene Quantum Dots: Synthesis of Blue‐, Green‐, Yellow‐, and Red‐Emitting Graphene‐Quantum‐Dot‐Based Nanomaterials with Excitation‐Independent Emission (Part. Part. Syst. Charact. 3/2016). (March 2016) - Ke, Chia‐Chun; Yang, Ya‐Chun; Tseng, Wei‐Lung
Abstract : As W. L. Tseng and co‐workers describe on page 132, graphene quantum dots (GODs)‐based nanomaterials with different colors can be prepared via hydroxyl radical‐induced decomposition of GO to small‐sized GO sheets and GQDs and heteroatom doping. The resulting GQD‐based nanomaterials exhibit size‐dependent emission, moderate quantum yield, excitation‐independent emission, high‐salt tolerance, and high photobleaching resistance, qualifying them for use in temperature sensors and cellular imaging.